Design of a Digital Teaching Material for Writing Fantasy Stories Based on Ethnopedagogy - Murti, Sri; Fitrah, Yundi; Kusmana, Ade (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
This study aims to design and develop ethnopedagogy-based digital teaching materials for teaching fantasy story writing in senior high school, with the objective of improving students’ creative writing skills while strengthening their appreciation of local culture. The research employed a Research and Development (R&D) approach adapted from the ADDIE model, encompassing needs analysis, design, development, implementation, and evaluation stages. The participants consisted of Grade X high school students and Indonesian language teachers. Data were collected through expert validation sheets, questionnaires, observation, writing tests, and interviews. The findings indicate that the developed digital teaching materials are highly valid in terms of content, language, and media design, practical for classroom implementation, and effective in enhancing students’ ability to write imaginative fantasy stories embedded with ethnopedagogical values. Students demonstrated significant improvement in narrative structure, creativity, and the integration of local wisdom elements into their writing. This study implies that ethnopedagogy-based digital teaching materials can serve as an effective instructional innovation to support culturally responsive literacy learning in secondary education. For research, the study contributes a practical R&D model for integrating local cultural values into digital literacy instruction. The novelty of this research lies in the integration of ethnopedagogical principles into digital fantasy story writing materials, offering a meaningful contribution to creative writing pedagogy and culturally grounded digital learning in the contemporary educational context.